CONVENIENCE PERCEPTION AND SECURITY ON INTEREST OF MSMEs IN USING QRIS - Rahmadi, Afif Nur; Hermawan, Agus; Putra, Yudiarto Perdana (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background. Global relations have become endless blessings? of progress technology information and communication, which have changed the economy, culture, and society in a way fast. System Service Provider Payment (PJSP) and Bank Indonesia have developed QRIS, one of which types non- non-cash payments, to reduce time and energy by replacing cash as a tool payment. With progress fast in system process technology payment, type cash payments become more efficient. Research Purpose. To know the impact of perception convenience use and security using QRIS against Micro, Small, and Medium Enterprises (MSMEs) actors. Research Methods. With the use approach quantitative research using the SEM-PLS method. Analyzed variables in the study. Research data was obtained through collected primary data through spread questionnaire and secondary data. The research sample consists of 55 respondents selected through a purposive sampling technique, with existing criteria for Micro, Small, and Medium Enterprises (MSMEs) using QRIS Findings. Convenience use has a significant impact on positive intention using QRIS. security own impact significant and positive intention using QRIS. Research R-Square value This of 0.805 which means 80.5% variance intention using QRIS can explained by the variables studied, while 19.5% is caused by other factors that aren’t used in this study. Perceived security appears as a dominant influential significant to intention use of QRIS, with a total impact highest of 0.699 compared with convenience. Conclusion. Convenience and security are influential and significant to use QRIS if respondents in each indicator question have a positive relationship to the decision to use QRIS.